2003
DOI: 10.1038/sj.hdy.6800299
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the tropical tree Terminalia amazonia (Combretaceae) in naturally fragmented populations

Abstract: The effect of long-term fragmentation on the genetic diversity of populations of the neotropical tree species, Terminalia amazonia, was studied using random amplified polymorphic DNA (RAPD) analysis. Leaf material from 104 trees was collected from three naturally fragmented gallery forest patches and three plots in nearby continuous forest in the Mountain Pine Ridge, Belize. In total, 30 RAPD bands generated by five decamer primers were used to compare the genetic diversity of the six populations in the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
3
28
0
8
Order By: Relevance
“…this pattern has been reported also in previous studies using RaPDs in tropical tree species (Cardoso et al, 1998;Pither et al, 2003). High variability in the tropical species of the lauraceae family has been associated with its dioeciousness, protogyny, insect pollination and animal-mediated seed dispersal (gibson & Wheelwright, 1995;moraes & monteiro, 2002), although low RaPD variability was recently reported in an endangered woody non-tropical lauraceae species (ZhongSheng et al, 2005).…”
Section: Distribution Of the Genetic Diversity In Rosewood Populationsmentioning
confidence: 75%
“…this pattern has been reported also in previous studies using RaPDs in tropical tree species (Cardoso et al, 1998;Pither et al, 2003). High variability in the tropical species of the lauraceae family has been associated with its dioeciousness, protogyny, insect pollination and animal-mediated seed dispersal (gibson & Wheelwright, 1995;moraes & monteiro, 2002), although low RaPD variability was recently reported in an endangered woody non-tropical lauraceae species (ZhongSheng et al, 2005).…”
Section: Distribution Of the Genetic Diversity In Rosewood Populationsmentioning
confidence: 75%
“…When phenological information on forest types is lacking , biased selection of seeds may limit genetic variability and increase the homogeneity of the regenerated stands [71]. Several studies have shown that shifting seeds from old-growth forests to disturbed landscapes can improve genetic variability in degraded landscapes [e.g., [73][74][75][76]. However, the germination and establishment of native tree seeds may be generally poor, perhaps due to the sudden shift in microclimatic and soil conditions [72].…”
Section: Direct Seedingmentioning
confidence: 99%
“…De Carvalho et al (2008) using RAPD markers reported high genetic variability in a population of Luehea divaricata Mart. found in a declivity area, while Pither et al (2003) found I values varying from 0.320 to 0.380 for Terminalia amazônia (J. Gmell) Exell. In Swietenia macrophylla King, Gillies et al (1999) found an I of 0.350, and Aide and Rivera (1998) found a value of 0.590 for Poulsenia armata (Miq.)…”
Section: Genetic Variability Of Samplesmentioning
confidence: 99%